Peran Orang Tua Tunggal dalam Menanamkan Nilai-Nilai Islam dan Tanggung Jawab Membesarkan Anak - Mukhlishah; Muhtadin; Komalasari, Euis (Lembaga Pengkajian Pengembangan Pendidikan dan Kewirausahaan, 2024)
This study aims to determine the role of single parents in the family to provide for, nurture and educate, and still try to teach Islamic values such as Mrs. Sumirah understands that a child is a gift from God, and describes the challenges and support she faces in her role as a single parent. Results of the study: Despite being busy taking care of her two children, Mrs. Sumirah continues to teach lessons in raising her children, especially Cecep who is healthy, teaches how to do ablution, prays as well as manners, and does not forget that she always reminds Cecep to respect and love Ahmad, his older brother. crippled since infancy. To test the validity of this research data, the researchers used triangulation. The research technique used is interview, observation, documentation. While the analysis of research data includes data reduction, data presentation, drawing conclusions. Based on the results of the research, it can be concluded: a wife whose husband has died remains tough, patient, and earns a living, is able to imitate the behavior of Mrs. Sumirah, no matter how busy she is, she still has time to instill Islamic values in her children, and the results of this study can be the best solution for another single parent.